Antigen‐specific Helios−, Neuropilin‐1− Tregs induce apoptosis of autoreactive B cells via PD‐L1. Issue 8 (2nd May 2018) - Gotot, Janine; Dhana, Ermanila; Yagita, Hideo; Kaiser, Romina; Ludwig‐Portugall, Isis; Kurts, Christian
Abstract: Regulatory T cells (Tregs) maintain self‐tolerance and prevent autoimmunity by controlling autoreactive T cells. We recently demonstrated in vivo that Tregs can directly suppress auto‐reactive B cells via programmed death ligand 1 (PD‐L1) that ligated PD‐1 on B cells and caused them to undergo apoptosis. Here, we asked whether this mechanism is utilized by thymus‐derived natural Tregs and/or by peripheral lymphoid tissue‐induced Tregs. We first demonstrated that antigen‐specific PD‐L1‐expressing Tregs were induced in the draining lymph node of autoantigen‐expressing tissue and characterized them by their lack of the transcription factor Helios and of the surface marker Neuropilin‐1 (Nrp‐1). Next, we established an in vitro co‐culture system to study the interaction between B cells and Treg subsets under controlled conditions. We found that Nrp − Treg, but not Nrp + Treg suppressed autoreactive B cells, whereas both were able to suppress T‐helper cells. Such suppression was antigen‐specific and was facilitated by PD‐L1/PD‐1‐induced apoptosis. Furthermore, it required physical cell contact and was MHC II‐restricted, providing an explanation for the antigen‐specificity of peripherally‐induced Tregs. These findings identify a role for peripherally induced Helios − Nrp‐1 − inducible Treg in controlling peripheral B‐cell tolerance against tissue auto‐antigens. Abstract : We recently demonstrated that Regulatory T cells (Tregs) can directly suppress auto‐reactive B cells via programmed death ligand 1 (PD‐L1) that ligated PD‐1 on B cells and caused them to undergo apoptosis. Here, we show that Nrp – peripherally expanded Treg, but not Nrp + thymic‐derived Treg suppressed autoreactive B cells, whereas both were able to suppress T‐helper cells. This was facilitated through PD‐L1/PD‐1 induced apoptosis in a contact‐, antigen‐ and MHC‐II‐dependent manner. These findings clarify the origin and subtype of Treg that specifically suppress autoreactive B cells.